The Use of Tiktok in Increasing Brand Awareness (Case Study on Mie Gacoan Followers in Medan) - Farah Fadhillah Khairani; Loula Umaiyah Indriana; Vrisya Dwi Tirabusky; Maulana Andinata Dalimunthe; Hasan Sazali (Penerbit Jurnal Indonesia, 2022)
The rapid development of internet technology, anyone can use it, anywhere and anytime without knowing boundaries. The development of the internet can also trigger emergence of various new social media, such as TikTok. TikTok itself is a social media platform that focuses on being a forum for video creator content communities, where each user can share their experiences and information through videos of a certain duration. In this study, the marketing mix theory and Uses and Gratification theory are used, which with these two theories will solve the problem of using TikTok in increasing brand awareness. The research method used is qualitative research, data obtained by interview and observation. From the results of research that has been researched, the TikTok Mie Gacoan account really utilizes the use of the TikTok application well and also in the application of marketing communications with the promotional mix is quite efficient and also effective for increasing brand awareness of the Mie Gacoan brand itself.